Determinan Ketepatan Kode Diagnosis Utama di RS Pusat Pertamina Jakarta Selatan - Nada Savira Nurjannah; Demiawan Rachmatta Putro Mudiono; Sustin Farlinda; Djasmanto Djasmanto (Jurnal Rekam Medik & Manajemen Informasi Kesehatan, 2022)
The inaccuracy of the main diagnosis code will have an impact on the hospital in terms of financing and the quality of the information produced. This can also be influenced by the accuracy of writing the main diagnosis. The purpose of this study was to determinants of the accuracy of the main diagnosis code in the discharged summary of inpatient in February 2022 at Pertamina Central Hospital by paying attention to several components, namely the clarity of writing the main diagnosis and the accuracy of the main diagnosis code. The method used is descriptive qualitative. The total sample is 130 of inpatient discharged summary sheets from a total of 463 medical record files in February 2022. The results showed that 42% discharge summary sheets were not clear in writing the main diagnosis and 86% the main diagnosis code did not correct. It is suggested that the hospital can improve the evaluation of the accuracy of filling in the code and writing the main diagnosis in the summary of discharge, holding training and seminars related to doctor's compliance with the ICD-10 code, and socializing how to enforce the code and write a diagnosis according to the ICD-10 rules.